Maternal thyroid hormone is required for parvalbumin neurone development in the anterior hypothalamic area. (27th February 2018) - Harder, L.; Dudazy‐Gralla, S.; Müller‐Fielitz, H.; Hjerling Leffler, J.; Vennström, B.; Heuer, H.; Mittag, J.
Abstract : Thyroid hormone (TH) is crucial for brain development and function. This becomes most evident in untreated congenital hypothyroidism, leading to irreversible mental retardation. Likewise, maternal hypothyroxinaemia, a lack of TH during pregnancy, is associated with neurological dysfunction in the offspring, such as autism and reduced intellectual capacity. In the brain, TH acts mainly through TH receptor α1 (TRα1). Consequently, mice heterozygous for a dominant‐negative mutation in TRα1 display profound neuroanatomical abnormalities including deranged development of parvalbumin neurones. However, the exact timing and orchestration of TH signalling during parvalbumin neurone development remains elusive. In the present study, we dissect the development of parvalbumin neurones in the anterior hypothalamic area (AHA) in male mice using different mouse models with impaired pre‐ and postnatal TH signalling in combination with bromodeoxyuridine birth dating and immunohistochemistry. Our data reveal that hypothalamic parvalbumin neurones are born at embryonic day 12 and are first detected in the AHA at postnatal day 8, reaching their full population number at P13. Interestingly, they do not require TH postnatally because their development is not impaired in mice with impaired TH signalling after birth. By contrast, however, these neurones crucially depend on TH through TRα1 signalling in the second half of pregnancy, when the hormone is almost exclusively provided by the mother. For the first time, our findings directly link a maternal hormone to a neuroanatomical substrate in the foetal brain, and underline the importance of proper TH signalling during pregnancy for offspring mental health. Given the role of hypothalamic parvalbumin neurones in the central control of blood pressure, the present study advocates the inclusion of cardiovascular parameters in the current discussion on possible TH substitution in maternal hypothyroxinaemia.